2022
DOI: 10.3390/antiox11071237
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Oxidative, Platelet, and Vascular Function in Chronic Users of Heat-not-Burn vs. Traditional Combustion Cigarettes

Abstract: Smoking is still a major cardiovascular risk factor, despite many public awareness campaigns and dedicated interventions. Recently, modified risk products (MRP), e.g., heat-not-burn cigarettes (HNBCs), have been introduced as surrogates of traditional combustion cigarettes (TCCs). Although these products are promoted as healthier than TCCs, few studies have been conducted to assess it. This work is a sex-focused sub-study of a prospective observational study in which apparently healthy chronic TCC smokers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The concentrated nicotine vapor was then diluted with air and evenly distributed to each chamber at a flow rate of 7 to 8 L/min. Flow rate was adjusted to achieve plasma cotinine levels (approximately 600 ng/mL), comparable to those observed in human combustible cigarette and novel tobacco product users ( 34 36 ). Nicotine exposure followed a 12 h on/12 h off schedule, overlapping with the dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrated nicotine vapor was then diluted with air and evenly distributed to each chamber at a flow rate of 7 to 8 L/min. Flow rate was adjusted to achieve plasma cotinine levels (approximately 600 ng/mL), comparable to those observed in human combustible cigarette and novel tobacco product users ( 34 36 ). Nicotine exposure followed a 12 h on/12 h off schedule, overlapping with the dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…This estimate is the same as that which was given in our rst paper, as no additional studies were found that included biomarkers satisfying the requirements for inclusion in the combined estimates. Two studies [19,20] not considered in our earlier estimate did provide data for blood pressure, body weight and cholesterol, while one study [21] provided data for blood pressure and body weight, and one [22] data for biomarkers of aminobiphenyl, naphthalene and toluene, but none of these biomarkers were considered adequate predictors to be considered in a combined analysis.…”
Section: Estimated Lung Cancer Relative Risks For Heated Tobacco Prod...mentioning
confidence: 96%
“…The third study investigated the role of gender in the cardiovascular effects of cigarette or HTP use [142].…”
Section: Cardiovascular System: Clinical Studiesmentioning
confidence: 99%
“…The third study investigated the role of gender in the cardiovascular effects of cigarette or HTP use [ 142 ]. The study comprised a gender-specific analysis of a previously published prospective observational study [ 143 ].…”
Section: Reviewmentioning
confidence: 99%